SISTEM KENDALI TEKANAN UDARA SEKUNDER PADA FORCED DRAFT FAN DI PLTU PAITON - Alfian Prasetyo Aji; Ilham Arifin Pahlawan (ENIGMA: Engineering in Green Machinery, 2025)
This research aims to assess the effectiveness of using Pressure Transmitters on the Force Draft Fan in a Steam Power Plant. The evaluation is conducted through a series of tests to measure air pressure and analyze the response of the Inlet damper position in regulating airflow. Data were collected through literature studies, direct field observations, and interviews with relevant practitioners. The measurement results show significant pressure variations. For a set point of 100 mmWG, the measured air pressure values range from 94.37 mmWG to 111.31 mmWG, and the percentage opening of the Inlet damper for FDF A & B varies between 58.28% to 63.07%. There are some measurement errors that need to be further evaluated, with error values ranging from -11.31 to 7,72 mmWG. Nevertheless, the system still operates within acceptable limits.